Cocrystallization of Imide‐Fused Corannulene Derivatives and C60: Guest‐Induced Conformational Switching and 1:1 Segregated Packing. Issue 19 (24th August 2018) - Lu, Ru‐Qiang; Wu, Shuang; Bao, Yue‐Hua; Yang, Lin‐Lin; Qu, Hang; Saha, Mithu; Wang, Xiao‐Ye; Zhuo, You‐Zhen; Xu, Binbin; Pei, Jian; Zhang, Hui; Weng, Wengui; et al.
Abstract: A pair of interconvertible stereoisomers of imide‐fused corannulene derivatives was mixed with C60, which resulted in cocrystallization into a 1:1 segregated packing motif through concave–convex π–π interactions. Only one conformation was observed in the cocrystal owing to guest‐induced conformational switching. The 1D assemblies of the complex showed promising applications in organic electronics. Abstract : Bowled over : C60 is used to tune the relative populations of two interconvertible stereoisomers of imide‐fused corannulene derivatives. Only one conformation is observed in the cocrystal owing to guest‐induced conformational switching. One‐dimensional assemblies with a 1:1 segregated packing motif of the complex show promising applications in organic electronics.